Analysis of Glycaemic Changes and their Outcome in Critically Ill Non-diabetic Patients Admitted to the ICU: A Cohort Study - Bharat Yadav; Vinod Kumar; Amit Nachankar (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Critical illness results in physiological and metabolic changes that lead to dysglycaemia, which is associated with morbidity and mortality. There exists a J- or U-shaped relationship between average glucose levels and mortality, emphasising the importance of evaluating glycaemic variability in critical illness. Aim: To assess glycaemic changes in critically ill patients and their association with Intensive Care Unit (ICU) outcomes. Materials and Methods: The prospective cohort study was conducted from August 2018 to August 2019. A total of 100 non-diabetic critically ill patients admitted to the ICU were observed for seven days. The severity of illness was evaluated using the Glasgow Coma Score (GCS) and Sequential Organ Failure Assessment (SOFA) scores. Plasma glucose levels were recorded every four hours in the ICU. Patients were followed for a maximum of seven days or until discharge or death. They were categorised into hypoglycaemia, normoglycaemia, or stress hyperglycaemia groups for analysis. Statistical analysis was performed using IBM SPSS Statistics for Windows, version 24.0. Results: The study included 64 male and 36 female patients, with an average mean age of 55.90±16.51 years (range: 18- 86 years). Among the 100 patients, 21 died within the sevenday hospitalisation period. Among these, two were in the hypoglycaemic group, 13 were in the normoglycaemic group, and six were in the stress hyperglycaemic group. The patients had a mean SOFA score of 11.55±2.20, which was significantly higher compared to patients without organ failure (mean score: 2.54±2.55), with a statistically significant association (p<0.01). Similarly, patients who died during hospitalisation had a very high SOFA score (mean score: 9.76±3.36), also statistically significant (p<0.01). Conclusion: Critically ill patients in the stress hyperglycaemia and hypoglycaemia groups during their ICU stay had a worse prognosis compared to patients with normoglycaemia. Hypoglycaemia during the ICU stay was associated with the poorest outcome. Maintaining normoglycaemia can significantly reduce morbidity and mortality in critically ill non-diabetic patients; therefore, considering Continuous Glucose Monitoring Systems (CGMS) for more frequent glycaemic monitoring and reducing glycaemic variability may lead to better outcomes in the ICU.